Catheter Ablation vs. Anti-Arrhythmic Drugs as First-Line Treatment in Symptomatic Paroxysmal Atrial Fibrillation: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Saglietto, Andrea; Gaita, Fiorenzo; De Ponti, Roberto; De Ferrari, Gaetano Maria; Anselmino, Matteo (Frontiers in Cardiovascular Medicine, 2021)
Background: Catheter ablation has become a well-established indication for long-term rhythm control in atrial fibrillation (AF) patients refractory to anti-arrhythmic drugs (AADs). Efficacy and safety of AF catheter ablation (AFCA) before AADs failure are, instead, questioned. Objective: The aim of the study was to perform a systematic review and meta-analysis of randomized clinical trials (RCTs) comparing first-line AFCA with AADs in symptomatic patients with paroxysmal AF. Methods: We performed a random-effects meta-analysis of binary outcome events comparing AFCA with AADs in rhythm control-naïve patients. The primary outcomes, also stratified by the type of ablation energy (radiofrequency or cryoenergy), were (1) recurrence of atrial tachyarrhythmias and (2) recurrence of symptomatic atrial tachyarrhythmias. The secondary outcomes included adverse events. Results: Six RCTs were included in the analysis. AFCA was associated with lower recurrences of atrial tachyarrhythmias [relative risk (RR) 0.58, 95% confidence interval (CI) 0.46–0.72], consistent across the two types of ablation energy (radiofrequency, RR 0.50, 95% CI 0.28–0.89; cryoenergy, RR 0.60, 95% CI 0.50–0.72; p-value for subgroup differences: 0.55). Similarly, AFCA was related to less symptomatic arrhythmic recurrences (RR 0.46, 95% CI 0.27–0.79). Overall, adverse events did not differ. A trend toward increased periprocedural cardiac tamponade or phrenic nerve palsy was observed in the AFCA group, while more atrial flutter episodes with 1:1 atrioventricular conduction and syncopal events were reported in the AAD group. Conclusions: First-line rhythm control therapy with AFCA, independent from the adopted energy source (radiofrequency or cryoenergy), reduces long-term arrhythmic recurrences in patients with symptomatic paroxysmal AF compared with AADs.